ASSESSMENT OF GENE PROFILES ASSOCIATED WITH PUNGENCY LEVELS IN CHILI (CAPSICUM SPP.) - Maneerattanarungroj, Chaichan; Sujipuli, Kawee; Khonthun, Chakkraphong; Laywisadkul, Srisangwan; Prasarnpun, Surisak (PSRU Journal of Science and Technology, 2021)
Chili in the genus Capsicum is globally cultivated as an economic vegetable crop, and used in traditionally pungent cuisines, especially in Thailand. Degrees of pungency were positively correlated with capsaicin biosynthesis, which was strongly influenced by genotype and associated with several enzyme-encoding genes. Five candidate genes (PUN1, HCT, pAMT, CCR and KAS) responsible for capsaicin synthesis were assessed among fourteen Capsicum cultivars. Results showed that all putative capsaicin biosynthetic genes were present in five Capsicum cultivars of Bhut Jolokia, Orange Habanero (High pungency) and Tubtim Mordindang, Phet Mordingang and Akanee Pirote (Moderate pungency). Two genes (HCT and pAMT) were absent in all eight low pungent cultivars (Jindanil 80, Bang Chang, Yodson Khem 80, Num Khao Donyang, Num Keowtong 80, Hua-ruea, Huai Si Thon Kham Kaen and Chai Tai). Analysis of the capsaicin biosynthetic genes showed that Capsicum cultivar KKU-P28016 (breeding line from Khon Kaen University) contained PUN1, pAMT, CCR and KAS genes, suggesting identity as the moderately pungent Capsicum group. Mature fruit phenotypic traits among the studied Capsicum cultivars showed that a globose-oval shape of mature fruit was detected among highly and moderately pungent Capsicum cultivars, while an elongated shape of mature fruit was observed in low pungent cultivars. High correlation between the phenotypic trait of mature fruit shape and gene profiles is a powerful tool to discriminate pungency levels in Capsicum cultivars.